FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSELOR SEBAYA DALAM IMPLEMENTASI KONSELING KESEHATAN REPRODUKSI REMAJA DI KABUPATEN SUMENEP - Dian Permatasari (Wiraraja Medika : Jurnal Kesehatan, 2013)
Teens are supposed to be the top priority of reproduction health who will probably determine quality level of reproduction health in the future. Globalization information brings big impact to the teens. Eagerness to know things related to reproduction push teens to search for information from many sources related their peer friends, parents, schools and mass media. For that, certain correct and responsible information are needed so that influences teens to have healthy reproduction habits. This research is aimed to analyze factors which influence peer counselor habit in the implementation of teens reproduction health in  Sumenep Regency. The kind of this research is analytical observation which is done quantitatively. The cross sectional approach is done in collecting data. Populations in this research are 66 at all peer counselors as total populations who ever joint Teen Reproduction Health Training in Sumenep Regency in year of 2012. Logistic regression and chi-square statistical analysis are used to analyze the data.The result of this research shows that peer counselor habits in the KRR counseling implementation mostly in about 69,7 % are good habits. As bivariate variables which is related to peer counselor habits in the KRR counseling implementation are knowledge (p=0,036), attitude (p=0,030), motivation (p=0,036), the Beside some free variables i.e age (p=0,248), sex/ gender (p=0,521), education (p=0,397), and information source access (p=0,594). Multivariate analysis result states that the most dominant influence factor is knowledge related to KRR counseling, motivation due to KRR counseling implementation due to KRR counseling implementation.This research is also recommended to Sumenep Regency’s KB and BPMP department to perform and activate teens reproduction health counseling training and inviting active peer counselors in Sumenep Regency, beside facilitate every KRR counseling activity related with medium and infrastructure.Keywords : knowledge, attitude, motivation, age, gender, education